Contemporary prevalence, in-hospital outcomes, and prognostic determinants of triple valve surgery: National database review involving 5, 234 patients. (August 2017) - Ohmes, Lucas B.; Kim, Luke; Feldman, Dmitriy N.; Lau, Christopher; Munjal, Monica; Di Franco, Antonino; Hameedi, Fawad; Gambardella, Ivancarmine; Girardi, Leonard N.; Gaudino, Mario
Abstract: Background: Triple valve surgery (TVS) remains a challenging procedure with limited existing literature. We aim to evaluate the prevalence, in-hospital outcomes, and prognostic determinants of TVS in the current era. Materials and methods: We reviewed the Nationwide Inpatient Sample database from 2003 to 2012 and included all patients who underwent aortic valve replacement (AVR) combined with mitral valve replacement (MVR) or repair (MVRep) and tricuspid valve replacement (TVR) or repair (TVRep). Logistic regression analysis was used to identify independent predictors of in-hospital mortality and propensity score matching was adopted to compare groups receiving different operations. Results: Overall, 5234 patients were included. In-hospital mortality was 13.9%. Major adverse events occurred in 42.9% of the cases (44.9%, 40.3%, 44.4% and 74.2% in the AVR + MVR + TVR, AVR + MVR + TVRep, AVR + MVRep + TVRep and AVR + MVRep + TVR groups respectively, p < 0.05 for all intergroup comparisons). In-hospital mortality in the AVR + MVR + TVR, AVR + MVR + TVRep, AVR + MVRep + TVRep and AVR + MVRep + TVR groups was 19.9%, 13.3%, 12.9% and 0% respectively (p < 0.05 for all intergroup comparisons). At regression analysis, age, reoperation, and urgent/emergent operation were independent predictors of in-hospital mortality. Patients submitted to tricuspid valve repair and mitral and tricuspid repair had a 62% and 63% mortality risk reduction (OR:0.380, CI:0.19–0.76 p = 0.006 and OR:0.37, CI:0.18–0.78 p = 0.009 respectively). In the propensity matched comparisons, in-hospital mortality was statistically similar (p = 0.08 for AVR + MVR + TVR vs. AVR + MVR + TVRep comparison and p = 0.06 for AVR + MVR + TVR vs. AVR + MVRep + TVRep comparison). Conclusions: TVS is associated with significant in-hospital mortality and morbidity. The use of valve repair strategies for the mitral and tricuspid valves can positively impact postoperative outcomes. Graphical abstract: Highlights: Little is known about the outcomes following triple valve surgery. Even in high volume centers the number of triple valve surgery performed is small. Pooling data from the National Inpatient Sample database helps overcome this limitation. Replacement strategies have high mortality and occurrence of major adverse events. Repair strategies, especially for the mitral and tricuspid valves, can reduce the risk of mortality.